ANALYSIS OF BLAST VIBRATION IMPACT AT PARAMBAHAN COAL MINE, WEST SUMATERA USING SQUARE ROOT SCALED DISTANCE METHOD - AGUS NUGROHO; WIROTO WIMBO PRIHONO; TATANG WAHYUDI (Indonesian Mining Journal, 2006)
Blasting which was conducted at Parambahan produced a series of blast vibrations that might be harmful to human safety and surroundings. Therefore, the vibrations need to be evaluated whether it was over permitted the threshold for human safety or not. One of analysis methods for this purpose is square root scaled distance. The principle of the proposed method is to assess blast vibration impact on the environment for the cases when the blasting for opening mine had been performed previously. Analysis results shows that blast vibrations at Parambahan is below the allowed threshold of blast vibration for environment. Using measurement distance from blast source of 20 to 2,000 m, the lowest measured vibration is 0.18 mm/s and the highest one is 21.0 mm/s. Those mean that blast-generated vibrations at Parambahan are still safe for human and surrounding environment.